Application of shotcrete constitutive model to the time dependent behavior of TBM tunnel lining - H. Shaalan, Heyam; Mohamad Ismail, Mohd Ashraf; Azit, Romziah (International Journal of Engineering and Technology, 2018)
Shotcrete is ordinary concrete applied to the surface under high pressure. It demonstrates a highly time-dependent behaviour after few hours of application. Traditional approaches assume a simple linear elastic behaviour using a hypothetical young modulus to investigate the time-dependency and creep effects. In this paper, a new constitutive model of shotcrete is applied to evaluate the time-dependent behaviour of a TBM tunnel lining and investigate the parameters that can influence this behaviour. The Shotcrete model is based on the framework of Elasto-plasticity and designed to model shotcrete linings more realistically. The basic data of Pahang-Selangor Raw Water Transfer Project is used for the analysis study. An attempt is made to investigate the influence of some input parameters of the shotcrete model on the time-dependent behaviour of the shotcrete lining. These parameters include the time-dependent stiffness/strength parameters, creep and shrinkage parameters and steel fibre parameters. The variation in shotcrete strength classes causes a noticeable influence on the development of shotcrete compressive strength with time, particularly during the first days of application. The creep and shrinkage strain cause a considerable reduction in the development of the shotcrete stress with time. The impact of steel fibre content is determined, and the result indicated that the development of plain shotcrete stresses with time is lower than that of the reinforced shotcrete. In addition, a comparison study is performed to analyse the tunnel lining behaviour using both shotcrete model and an elastic analysis. Significant differences in shotcrete lining stresses are achieved when using the elastic analysis while the shotcrete model results in a reasonable result that can be used for the design requirements.Â